Optimizing Maintenance Cycle Time to Improve System Availability and Reduce Loss Production Opportunity in Water Injection Pump Benar Gathering Station (The Indonesian Journal of Business Administration, 2021)
PT. BLUE is one of the largest oil and gas companies in the world and have business unit that Operates in Sumatra. PT BLUE's operational area in Sumatra is known as the block rokan. The rokan block consists of several areas, namely: Bangko - Balam area, Bekasap area, and also Duri area. Each of these areas has several places for the process of collecting oil or better known as the Gathering Station. One of the most well-known gathering stations in Bangko - Balam Area is Benar GS. Benar GS is a gathering station which is also a contributor to producing oil which is large enough for Bangko - Balam Area. Benar GS has several equipment to help produce sufficient oil, including the Water Injection Pump (WIP), where there are 5 water injection pumps (WIPs) in the Benar GS area at the moment. This water injection pump is really needed to be able to inject water into the well to be able to push the fluids (water, oil and gas) in the well to the surface so that it can be processed later at the Gathering Station. In 2019 - 2020, there were 16 failures that occurred in the Water Injection Pump at this Benar GS. Problems such as an increase in temperature at the Water Injection Pump, the vibration that occurs in the Water Injection Pump which is caused by a lack of pressure suction on the Water Injection Pump and also problems in the electrical system such as problems with voltage and operating load for WIP. This problem causes WIP to shut down for a long time so that it will cause a loss of production oil (LPO) which is quite large with an average LPO that occurs at 682.5 BOPD. Therefore, a system that is able to increase the availability of Water Injection Pump is needed and reduce cycle time to repair if there is damage to the WIP so that it can reduce the loss of production oil (LPO) caused by WIP. The lean sigma method will be used in this case, where with this method a monitoring system will be produced which can be used as a reference for carrying out predictive maintenance so that it can prevent the Water Injection Pump (WIP) from experiencing long damage so that the LPO is the also get reduced. The results obtained from this improvement were a decrease in the number of failures that occurred at WIP in 2021 to 2 failures with an average LPO of 195 BOPD.Keywords: Availability, Cycle time, Lean Sigma, Loss production, Predictive Maintenance